Pediatric-type follicular lymphoma in adolescence: A case series - Uche C. Ezeh; Naomi Tesema; Sukaina Hasnie; Zahrah Taufique; Nicholas Ward; Max M. April (Elsevier, 2024)
Introduction: Pediatric-type follicular lymphoma (PTFL) is a rare B-cell lymphoma that primarily affects the head and neck, accounting for approximately 1.5-2% of childhood lymphomas. Distinguishing between follicular lymphoma and PTFL is critical due to their distinct clinical characteristics, which influence prognosis and treatment. Case presentation: Two patients, a 14-year-old male (Case 1) and a 17-year-old male (Case 2), presented to the pediatric otolaryngology clinic with complaints of an isolated neck and parotid masses, respectively. In Case 1, physical examination revealed a 5 cm upward-growing neck mass without accompanying B symptoms or discomfort. CT scan, needle biopsy, and MRI with contrast confirmed the presence of the mass, which was subsequently surgically excised. In Case 2, the patient had an enlarging left-sided parotid mass, along with night sweats, fatigue, and arthralgias. Ultrasound and contrast-enhanced MRI confirmed a well-defined solid vascular mass within the left parotid gland, which was subsequently surgically excised. Pathological examination confirmed PTFL in both cases, leading to a positron emission tomography (PET)/CT scan for further evaluation and staging. Conclusion: This case series underscores the importance of pediatric surgeons to consider PTFL in the differential diagnosis of head and neck masses, as it can be effectively cured through surgical excision.